PERDEBATAN ASPEK-ASPEK KETUHANAN DALAM TEOLOGI DAN KAITANNYA DENGAN KALIMAT TAUHID - Sabara, Sabara (AL-Fikr, 2015)
The History of Islamic thought Â by some schools of kalam (theology) who have different views with one another. Differences in views on the different schools of kalam theology in Islam is based on the difference manhaj or epistemology to understand and believe in the existence of God. The concept of divinity of each of the flow of Islamic theology in different and sometimes diametrically opposed in interpreting sentences shared Tawhid, which is La ilaha illallah as an axiom in Islamic theology.Â Not only difference of interpretation at the level of mere theological concepts, but also implications for the realm of social applications of these theological views. So the difference in the attitude of life is largely determined by differences in theological outlook.